Discussing energy volatility and policy in the aftermath of the Russia–Ukraine conflict - Enescu, Adrian-Gabriel; Szeles, Monica Răileanu (Frontiers in Environmental Science, 2023)
The ongoing Russo–Ukrainian War has highly affected energy markets in the EU and worldwide, with different EU- and country-level emergency policy measures being advanced to tackle high energy prices. Despite the progress in green energy initiatives and the race toward climate neutrality by 2050, high energy prices are a matter of concern for all EU countries in the short-to-medium term. The current study investigates the energy price volatility in the aftermath of the Russia–Ukraine conflict, which is of high interest for designing effective government measures (such as monetary and energy policies) addressing the consequent changes occurring in employment, economic activity, commodity and food prices, and, ultimately, sustainable development. For the empirical analysis, we employed generalized autoregressive conditional heteroskedasticity models to capture the volatility of the following energy commodities: Brent crude oil, TTF natural gas, and UK natural gas. The empirical results reveal an elevated degree of persistence of the volatility, namely, that the generalized autoregressive conditional heteroskedasticity term has a slow decay and pronounced fluctuations for all the energy products. The vulnerability of the EU’s energy policy to geopolitical factors is highlighted, especially for gas, which could be due to its dependence on Russian imports. Moreover, the sanctions imposed by the EU on Russia, namely the sixth package of sanctions, have a minimal immediate effect on stabilizing energy returns. The study offers several policy recommendations to improve the resilience of the EU’s energy sector.